Essential oil composition from twelve varieties of basil (Ocimum spp) grown in Colombia - Viña,Amparo (2003)
Essential oil compositions of aerial parts from twelve basil cultivars (Ocimum spp) were analysed by gas chromatography-mass spectrometry (GC-MS). Ten of them were characterized by the presence of a high percentage of methyl cinnamate (35-80%), which defined the chemotype for these varieties. Only one presented the caryophyllene chemotype and another, the linalool chemotype. Three of the basils, "purple ruffles", "little virgin" and "purple virgin" exhibited the methyl cinnamate > linalool subtype. "White compact" and "white ruffles" showed the methyl cinnamate > linalool > 1,8-cineole subtype. Methyl cinnamate > methyl eugenol was the subtype for "purple castle". The variety "large green leaves" exhibited the linalool > methyl cinnamate subtype. Caryophyllene > methyl eugenol subtype was determined for "clove basil". The rest of the basils "cinnamon", "purple lovingly", "sweet castle" and "purple long-legged", belonged to the methyl cinnamate chemotype in which methyl cinnamate constituted more than 62% of the total essential oil content.